EVALUATION OF THE EFFECTIVENESS OF SIMULATION TRAINING IN TEACHING HEART AND LUNG AUSCULTATION - Parpibaeva Dinara Ayupovna, Ergashov Nodirbek Shermukhamat ugli, Salaeva Muborak Saidabdullaevna, Salimova Nargiza Djurabaevna, Buvamukhamedova Nasiba Takhirovna (American Journals, 2023)
The use of simulation technology for training and assessment in medical education has been increasing over the past decade. However, the training effectiveness of most simulators needs to be fully evaluated. The purpose of this prospective study was to evaluate whether brief individual training in a patient simulator could improve cardiac and pulmonary auscultation skills in undergraduate students.
Keywords: Simulation, medical education, cardiac auscultation, pulmonary auscultation.